ESTUDO DAS PROPRIEDADES FÍSICO-QUÍMICAS DOS ÓLEOS DE EUCALIPTO, LARANJA, SUCUPIRA, ABACATE E UVA - Francielly Anjolin Lescano (2024)
Vegetable and essential oils are composed of essential fatty acids (oleic and linoleic), antioxidants that fight free radicals. In this way, the use of these oils provides positive effects to the human body. Therefore, the objective of this research was to study the composition of vegetable and essential oil and their thermo-oxidative properties of Avocado, Eucalyptus, Sweet Orange, Sucupira and Grape Seed oils. The methods performed were: Differentiated Scanning Calorimetry (DSC), gas chromatography, determination of the induction period, UV/VIS spectroscopy and fluorescence. DSC curves of avocado oil presented two exothermic transitions, while eucalyptus, sucupira A and B, and grape seed A and B oils only showed a single exothermic transition. Saturated fatty acids with the highest percentage: orange (99.02%) and eucalyptus (99.97%), avocado vegetable oil (63.04%) of unsaturated fatty acids and grape seed B vegetable oil with (69.85%) of polyunsaturated fatty acids. Induction period of avocado vegetable oil 12.31h and grape seed A 6.18h. UV/Vis spectroscopy the essential oils of eucalyptus, orange and sucupira A are noticeable in the bands close to 225 to 280 nm. Fluorescence spectroscopy identified the presence of cinnamic acid, tyrosol, tocopherols, carotenoids and chlorophyll. In short, distinct behaviors were observed among them, resulting from variations in their chemical elements and proportions, the absence or reduced presence of compounds can interfere in the oxidative stability and preservation of the molecules.